Digital forums as pedagogical tool on building and (re)signification of knowledges in the scholar enviroiment - Sá Britto, Natália Daniela Soares; Manfroi, Pedro Cipriani (Revista Ensino de Geografia (Recife), 2019)
This article deals with the relevance of the Virtual Learning Environment (AVA) as a potentialtool for pedagogical processes in face-to-face mode, especially regarding the efficiency of using digital forums as a collaborative learning and knowledge management activity. For this, it presents an experience of incorporating new “times and spaces” in the school environment through AVA as a strategy for the development of ethical, aesthetic and political skills and competences related to decision-making, strategy formulation, interaction of knowledge, collaboration, planning and problem management. This experiment was carried out with the students of the 1st year of high school of the Marist College Pio XII, in Novo Hamburgo (RS), in the curriculum component of Geography, whose thematic axis is the resolution of situations-problems related to the eutrophication of the natural environment